Intermediate transfer belt, and image forming apparatus using the same

By designing the inner substrate and outer elastic layer structure on the intermediate transfer belt, combining spherical particles and ionic conductive agent, the problems of the intermediate transfer belt in high-speed printing and adaptability of different paper surfaces are solved, and high durability and efficient transfer effects are achieved.

JP2025018227APending Publication Date: 2025-02-06RICOH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023121746
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

When printing and processing papers on different surfaces at high speed, there are problems of uneven transfer, color shift and insufficient durability, especially when using polymer resin materials, high surface hardness leads to incomplete local transfer, and poor durability and adaptability to different paper surfaces.

Method used

An intermediate transfer belt structure is adopted, which includes an inner base layer and an outer elastic layer. The outer layer is composed of uniformly distributed spherical particles. The elastic layer uses acrylic rubber and an ionic conductive agent containing bis(trifluoromethanesulfonyl)imide to ensure that the particles do not detach and improve conductivity.

Benefits of technology

High durability and efficient transfer are achieved, particle detachment and ionic conductive agent deposition are avoided, adapted to different paper surfaces, and improved printing quality and equipment stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018227000002
    Figure 2025018227000002
  • Figure 2025018227000003
    Figure 2025018227000003
  • Figure 2025018227000004
    Figure 2025018227000004
Patent Text Reader

Abstract

To provide an intermediate transfer belt with high durability.SOLUTION: To an intermediate transfer belt, a toner image is transferred which is obtained by developing a latent image formed on an image carrier with toner. The intermediate transfer belt has a lamination structure including, sequentially from the inside, at least a base layer, and an elastic layer having an irregular shape formed by spherical particles on its outer surface. The elastic layer includes acrylic rubber and an ion conductive agent. An anion component of the ion conductive agent is bis(trifluoromethane sulfonyl)imide (TFSI).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an intermediate transfer belt and an image forming apparatus using the intermediate transfer belt. [Background technology]

[0002] Seamless belts have been used as components in electrophotographic devices for various purposes. In particular, in recent full-color electrophotographic devices, an intermediate transfer belt system is used in which four developed images of yellow, magenta, cyan, and black are first superimposed on an intermediate transfer medium and then transferred all at once to a transfer medium such as paper.

[0003] This type of intermediate transfer belt method was used in a system that used four color developers for one photoconductor, but had the drawback of slow printing speed. Therefore, for high-speed printing, a four-tandem method is used in which four photoconductors are lined up and each color is transferred to the paper in succession. However, with this method, the paper's properties vary depending on the environment, making it very difficult to align the positions of the overlapping color images, resulting in color misalignment. For this reason, it has become mainstream to use the intermediate transfer method in the four-tandem method in recent years.

[0004] In this situation, the required characteristics (high-speed transfer, positional accuracy) of intermediate transfer belts are becoming stricter than ever before, and it is becoming necessary to satisfy the characteristics corresponding to these requirements. In particular, for the positional accuracy, it is required to suppress fluctuations due to deformation such as elongation of the belt itself due to continuous use. In addition, intermediate transfer belts are laid out over a wide area of ​​the device, and are required to be flame-retardant because high voltages are applied for transfer. In order to meet such requirements, polyimide resins, polyamide-imide resins, and the like, which are resins with high elasticity and high heat resistance, are mainly used as intermediate transfer belt materials.

[0005] However, since intermediate transfer belts made of polyimide resin have high strength and therefore high surface hardness, when a toner image is transferred, high pressure is applied to the toner layer, which causes the toner to locally aggregate and result in a part of the image not being transferred, resulting in a so-called hollow image.In addition, since the contact follow-up ability with contact members such as the photoconductor and paper at the transfer section is poor, partial contact failures (gaps) occur at the transfer section, which can result in uneven transfer.

[0006] In recent years, full-color electrophotography has been used to form images on various types of paper, and not only normal smooth paper but also slippery, smooth paper such as coated paper, and rough paper such as recycled paper, embossed paper, Japanese paper, and craft paper are increasingly being used. The ability to conform to such papers with different surface properties is important, and poor conformability will cause unevenness in the shading and color tone of the paper. To solve this problem, various intermediate transfer belts have been proposed in which a relatively flexible rubber elastic layer is laminated on a base layer.

[0007] To solve this problem, there is a method of providing a new protective layer. However, if a material with sufficiently high transferability is coated, it cannot follow the flexibility of the flexible layer, and there is a problem that cracks and peeling occur, which is not preferable. For this reason, a proposal has been made to improve transferability by attaching fine particles to the surface.

[0008] Patent Document 1 proposes covering the surface of the intermediate transfer belt with beads having a diameter of 3 μm or less. Patent Document 2 proposes forming the surface of the intermediate transfer belt from a material having an affinity with hydrophobized fine particles, and providing a layer of hydrophobized fine particles on the surface of the intermediate transfer belt. Patent Document 3 proposes making the cylindrical belt constituting the intermediate transfer belt a three-layer structure consisting of a belt base layer, a binder layer, and a fine particle layer.

[0009] Patent Documents 4 and 5 propose that in a conductive endless belt constituting an intermediate transfer belt, the layer forming the belt surface is made of a thermoplastic resin as a main component, and that powder having a diameter smaller than the toner particle diameter is embedded over the entire surface of the layer made of the thermoplastic resin as a main component, with at least a portion of the layer exposed. Patent Document 6 proposes laminating a surface layer on rubber, adding bis(trifluoromethanesulfonyl)imide (TFSI) to the rubber, and adding particles for forming roughness to the surface layer. Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in consideration of the above-mentioned conventional technology, and aims to provide an intermediate transfer belt that has excellent transferability to paper types with uneven surfaces, does not experience detachment of spherical particles from the transfer body surface even after long-term use, and is highly durable, with no deposition of ion conductive agent. [Means for solving the problem]

[0011] As a result of extensive investigations, the present inventors have found that an intermediate transfer belt having the following configuration can solve the above problems. An intermediate transfer belt onto which a toner image obtained by developing a latent image formed on an image carrier with a toner is transferred, The intermediate transfer belt has a laminated structure including, from the inside, a base layer and an elastic layer having an uneven surface formed of spherical particles on the outer surface, in that order. the elastic layer contains an acrylic rubber and an ionic conductive agent, The anion component of the ion conductive agent is bis(trifluoromethanesulfonyl)imide (TFSI). The intermediate transfer belt is characterized by the above-mentioned. Effect of the Invention

[0012] According to the present invention, it is possible to provide an intermediate transfer belt having high durability, in which no spherical particles are detached even at the edge of a paper, and no ion conductive agent is precipitated. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of the shape of a particle. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of the shape of a particle. [Diagram 3] FIG. 3 is a diagram showing a schematic diagram of the shape of a particle. [Figure 4] FIG. 4A is an enlarged schematic diagram showing a cross section of the intermediate transfer belt, and FIG. 4B is an enlarged schematic diagram showing the surface of the intermediate transfer belt observed from above. [Diagram 5] FIG. 5 is a schematic diagram showing a method of applying particles to an elastic layer. [Figure 6] FIG. 6 is a schematic diagram showing an example of an image forming apparatus of the present invention. [Figure 7] FIG. 7 is a schematic diagram showing another example of the image forming apparatus of the present invention. BEST MODE FOR CARRYING OUT THEINVENTION

[0014] Seamless belts are used for several members in an image forming apparatus, and one of the important members that requires electrical properties is the intermediate transfer body (intermediate transfer belt). The intermediate transfer belt of the present invention will now be described.

[0015] The intermediate transfer belt of the present invention is suitably installed as an intermediate transfer belt in an image forming apparatus using an intermediate transfer belt system (a so-called apparatus using a system in which a plurality of color toner developed images formed in sequence on an image carrier (e.g., a photosensitive drum) are sequentially superimposed on an intermediate transfer belt to perform primary transfer, and the primary transferred images are then secondarily transferred collectively onto a recording medium).

[0016] 4A and 4B show the layer structure of an intermediate transfer belt preferably used in the present invention. The structure is such that a flexible elastic layer 12 is laminated on a rigid base layer 11 that provides relatively good flexibility, and spherical particles 13 are independently arranged (embedded) in the surface direction on the elastic layer on the outermost surface thereof, and are laminated to form a uniform uneven shape. When the spherical particles 13 in the present invention are not aggregated and exist as single particles, there is almost no overlap between the particles in the layer thickness direction or complete embedment in the elastic layer 12.

[0017] <base layer> First, a description will be given of the base layer 11. Examples of the constituent material of this include resin containing a filler (or an additive) that adjusts electrical resistance, that is, a so-called electrical resistance adjuster. From the viewpoint of flame retardancy, preferred resins of this type include fluororesins such as PVDF and ETFE, polyimide resins, and polyamideimide resins. From the viewpoint of mechanical strength (high elasticity) and heat resistance, polyimide resins and polyamideimide resins are particularly suitable.

[0018] Examples of the electrical resistance adjusting material include metal oxides, carbon black, ion conductive agents, conductive polymer materials, etc. Examples of the metal oxides include zinc oxide, tin oxide, titanium oxide, zirconium oxide, aluminum oxide, silicon oxide, etc. Examples of the metal oxides include those that have been previously surface-treated to improve dispersibility. Examples of the carbon black include Ketjen black, furnace black, acetylene black, thermal black, gas black, etc. Examples of the ion conductive agent include tetraalkylammonium salts, trialkylbenzylammonium salts, alkylsulfonates, alkylbenzenesulfonates, alkylsulfates, glycerin fatty acid esters, sorbitan fatty acid esters, polyoxyethylene alkylamines, polyoxyethylene fatty alcohol esters, alkyl betaines, lithium perchlorate, etc., and these may be used in combination. The electrical resistance adjusting material in the present invention is not limited to the above-mentioned exemplary compounds. In the method for producing an intermediate transfer belt of the present invention, the coating liquid containing at least a resin component may further contain additives such as a dispersion aid, a reinforcing material, a lubricant, a heat conductive material, and an antioxidant, if necessary.

[0019] When a seamless belt is used as the intermediate transfer belt, the resistance value is preferably 1×10 8 ~1×10 13 Ω / □, volume resistance is 1×10 8 ~1×10 11 The amount of carbon black to be added is such that the film has a resistivity of Ω·cm, but an amount that can be added is selected so that the film does not become brittle and prone to cracking in terms of mechanical strength. In other words, when used as an intermediate transfer belt, it is preferable to manufacture and use a seamless belt that has a good balance between electrical properties (surface resistance and volume resistance) and mechanical strength by using a coating liquid in which the blend of the resin component (e.g., polyimide resin precursor or polyamideimide resin precursor) and electrical resistance adjuster is properly adjusted.

[0020] The thickness of the base layer is not particularly limited and can be appropriately selected according to the purpose, but is preferably 30 μm or more and 150 μm or less, more preferably 40 μm or more and 120 μm or less, and particularly preferably 50 μm or more and 80 μm or less. If the thickness of the base layer is less than 30 μm, the belt is easily torn due to cracks, and if it exceeds 150 μm, the belt may break due to bending. On the other hand, if the thickness of the base layer is in the particularly preferred range, it is advantageous in terms of durability. With regard to the base layer, it is preferable to eliminate thickness unevenness as much as possible in order to improve running stability.

[0021] The method for adjusting the thickness of the base layer is not particularly limited and can be appropriately selected depending on the purpose. For example, the thickness can be measured using a contact or eddy current film thickness meter or by measuring the cross section of the film using a scanning electron microscope (SEM).

[0022] The content of the electrical resistance adjuster in the present invention is 10% by mass or more and 25% by mass or less, preferably 15% by mass or more and 20% by mass or less, of the total solid content in the coating liquid, in the case of carbon black. The content of the metal oxide is 1% by mass to 50% by mass, preferably 10% by mass or more and 30% by mass or less, of the total solid content in the coating liquid. If the content is less than the range of each of the electrical resistance adjusters, it becomes difficult to obtain uniformity in the resistance value, and the fluctuation of the resistance value at an arbitrary potential becomes large. If the content is more than the range, the mechanical strength of the intermediate transfer belt decreases, which is not preferable for practical use.

[0023] As the polyimide and polyamideimide in the present invention, general-purpose products can be obtained and used from manufacturers such as DuPont Toray, Ube Industries, New Japan Chemical, JSR, Unitika, IST, Hitachi Chemical, Toyobo, and Arakawa Chemical.

[0024] <Elastic layer> Next, the elastic layer 12 to be laminated on the base layer 11 will be described. The most preferable material for the elastic layer 12 is acrylic rubber, which has ozone resistance, flexibility, adhesion to spherical particles, flame retardancy, environmental stability, and affinity with bis(trifluoromethanesulfonyl)imide. The acrylic rubber will be described below.

[0025] The acrylic rubber (ACM) of the rubber elastic layer of the present invention may be any currently available commercially, and is not particularly limited. However, among the various crosslinking systems of acrylic rubber (epoxy group, active chlorine group, carboxyl group), the carboxyl group crosslinking system is superior in rubber physical properties (especially compression set) and processability, so it is preferable to select the carboxyl group crosslinking system.

[0026] The crosslinking agent used for the carboxyl group crosslinking acrylic rubber is preferably an amine compound, and most preferably a polyamine compound. Specific examples of such amine compounds include aliphatic polyamine crosslinking agents and aromatic polyamine crosslinking agents. Examples of aliphatic polyamine crosslinking agents include hexamethylenediamine, hexamethylenediamine carbamate, and N,N'-dicinnamylidene-1,6-hexanediamine.

[0027] Examples of aromatic polyvalent amine crosslinking agents include 4,4'-methylenedianiline, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-(m-phenylenediisopropylidene)dianiline, 4,4'-(p-phenylenediisopropylidene)dianiline, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminobenzanilide, 4,4'-bis(4-aminophenoxy)biphenyl, m-xylylenediamine, p-xylylenediamine, 1,3,5-benzenetriamine, and 1,3,5-benzenetriaminomethyl.

[0028] The amount of the crosslinking agent added is preferably 0.05 parts by mass or more and 20 parts by mass or less, and more preferably 0.1 parts by mass or more and 5 parts by mass or less, based on 100 parts by mass of the acrylic rubber. If the amount of crosslinking agent is too small, crosslinking will not be sufficient, making it difficult for the crosslinked product to maintain its shape, whereas if the amount is too large, the crosslinked product will be too hard, losing the elasticity and other properties of crosslinked rubber.

[0029] In the acrylic rubber elastic layer of the present invention, a crosslinking accelerator may be further blended and used in combination with the above crosslinking agent. The crosslinking accelerator is not limited, but is preferably a crosslinking accelerator that can be used in combination with the polyvalent amine crosslinking agent. Examples of such crosslinking accelerators include guanidine compounds, imidazole compounds, quaternary onium salts, tertiary phosphine compounds, and alkali metal salts of weak acids. Examples of guanidine compounds include 1,3-diphenylguanidine and 1,3-diorthotolylguanidine. Examples of imidazole compounds include 2-methylimidazole and 2-phenylimidazole. Examples of quaternary onium salts include tetra-n-butylammonium bromide and octadecyl tri-n-butylammonium bromide. Examples of polyvalent tertiary amine compounds include triethylenediamine and 1,8-diaza-bicyclo[5.4.0]undecene-7 (DBU). Examples of tertiary phosphine compounds include triphenylphosphine and tri-p-tolylphosphine. Examples of the alkali metal salts of weak acids include inorganic weak acid salts such as sodium or potassium phosphates and carbonates, and organic weak acid salts such as stearates and laurates.

[0030] The amount of the crosslinking accelerator used is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, per 100 parts by mass of acrylic rubber. If the amount of the crosslinking accelerator is too much, the crosslinking speed may be too fast during crosslinking, the crosslinking accelerator may bloom on the surface of the crosslinked product, or the crosslinked product may become too hard. If the amount of the crosslinking accelerator is too little, the tensile strength of the crosslinked product may be significantly reduced, or the change in elongation or tensile strength after heat load may be too large.

[0031] <Ionic conductive agent> Examples of ionic conductive agents include various perchlorates and ionic liquids, but from the viewpoint of particle detachment and surface precipitation (so-called bleed and bloom), ionic conductive agents having an anion component of bis(trifluoromethanesulfonyl)imide are preferred. The cationic component to be combined with the anion component is not particularly limited, but examples include butylbishydroxyethylmethylammonium, ethylmethylimidazolium, butyl-3-methylpyridinium, and diallyldimethylammonium. Among these, butylbishydroxyethylmethylammonium is particularly preferred from the viewpoint of suppressing particle detachment and preventing surface precipitation. Examples of commercially available products of such materials include CIL-312, 512, 612, and R10 from Nippon Carlit.

[0032] <Other additives: flame retardants> Other additives include flame retardants. Examples of flame retardants include metal hydrates such as aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium hydroxide, zirconium hydroxide, dolomite, hydrotalcite, and zinc hydroxystannate. Among them, aluminum hydroxide and magnesium hydroxide can particularly improve the flame retardancy of acrylic rubber. Furthermore, aluminum hydroxide and magnesium hydroxide do not impair the tackiness of acrylic rubber. Therefore, a synergistic effect of improving the flame retardancy and adhesion of the intermediate transfer belt can be obtained. In particular, aluminum hydroxide has excellent dispersibility in rubber, is advantageous in terms of flame retardancy and resistance to environmental changes, and is particularly preferred in terms of affinity with bis(trifluoromethanesulfonyl)imide. Examples of commercially available products of such aluminum hydroxide include BF013, B1403, and B703 from Nippon Light Metal Co., Ltd.

[0033] From the viewpoint of improving flame retardancy and adhesion between spherical particles and acrylic rubber, the average particle size of the metal hydrate of the flame retardant is preferably 0.1 μm to 10 μm, more preferably 1.0 μm to 3 μm. The amount of flame retardant added is 10 parts by mass to 80 parts by mass, particularly preferably 30 parts by mass to 70 parts by mass. If it is less than 10 parts by mass, the flame retardant effect is small, and if it exceeds 80 parts by mass, the flexibility of the acrylic rubber is impaired.

[0034] In preparing the acrylic rubber, a suitable mixing method such as roll mixing, Banbury mixing, screw mixing, solution mixing, etc. The order of mixing is not particularly limited, but after thoroughly mixing the components that are difficult to react or decompose by heat, components that are easy to react or decompose by heat, such as a crosslinking agent, may be mixed for a short time at a temperature at which they do not react or decompose.

[0035] The acrylic rubber can be crosslinked by heating. The heating temperature is preferably 130°C to 220°C, more preferably 140°C to 200°C, and the crosslinking time is preferably 30 seconds to 5 hours. The heating method may be appropriately selected from methods used for crosslinking rubber, such as press heating, steam heating, oven heating, and hot air heating. After crosslinking once, post-crosslinking may be performed to ensure crosslinking to the inside of the crosslinked product. The post-crosslinking time varies depending on the heating method, crosslinking temperature, shape, etc., but is preferably performed for 1 hour to 48 hours. The heating method and heating temperature when performing post-crosslinking may be appropriately selected.

[0036] The flexibility of the rubber elastic layer is preferably such that the micro hardness value at 25°C and 50% RH is 30 to 80. The micro hardness can be measured using a commercially available micro hardness tester, for example, the "Micro Hardness Tester MD-1" manufactured by Kobunshi Keiki Co., Ltd.

[0037] On the other hand, the thickness of the elastic layer is preferably 200 μm to 600 μm, more preferably 300 μm to 400 μm. By being 200 μm or more, the image quality for paper types with surface irregularities is sufficient, and by being 600 μm or less, the elastic layer is preferably not heavy, prone to bending, or warped to a large extent, which makes running unstable. As a method for measuring the thickness, a cross section can be measured using a scanning electron microscope (SEM).

[0038] <Spherical particles> Next, the spherical particles formed on the surface of the elastic layer will be described. There is no particular restriction on the material of the spherical particles, but they may be insulating resin particles or conductive metal particles, or a multi-layer structure in which the surfaces of insulating resin particles are coated or polymerized with a conductive resin or plated with a metal to increase conductivity may be used. Examples of materials for insulating particles include acrylic resins such as polymethyl methacrylate and polymethyl acrylate, polyolefin resins such as polyethylene, polypropylene, polyisobutylene, and polybutadiene, polystyrene resins, melamine resins, silica, silicone resins, and fluororesins. Examples of metal particles include metals such as gold, silver, copper, platinum, zinc, iron, palladium, nickel, tin, chromium, titanium, aluminum, cobalt, germanium, and cadmium, and compounds such as ITO and solder. One type of particle or a mixture of two or more types may be used, but among these, acrylic resin particles, which are difficult to separate from acrylic rubber and have high affinity with bis(trifluoromethanesulfonyl)imide, are particularly preferred.

[0039] The shape of the particles is preferably a spherical particle from the viewpoint of toner transfer efficiency. If the particles are not spherical, they tend to fall off easily and the effect of suppressing particle fall off is not achieved. In the present invention, the truly spherical particles are defined as follows. 1 to 3 are diagrams showing schematic shapes of particles used in the present invention. In Figures 2 and 3, when a particle is defined by a major axis r1, a minor axis r2, and a thickness r3 (where r1 ≧ r2 ≧ r3), a particle is defined as being spherical if the ratio of the major axis to the minor axis (r2 / r1) is in the range of 0.9 to 1.0 and the ratio of the thickness to the minor axis (r3 / r2) is in the range of 0.9 to 1.0. If the ratio of the major axis to the minor axis and the ratio of the thickness to the minor axis (r3 / r2) are less than 0.9, it becomes difficult to align the toner particles on the surface of the elastic layer, resulting in a decrease in the transfer efficiency of the toner. The long axis r1, short axis r2, and thickness r3 can be determined, for example, by uniformly dispersing and attaching particles on a smooth measurement surface, and measuring the long axis r1 (μm), short axis r2 (μm), and thickness r3 (μm) of 100 particles at an arbitrary magnification (for example, 1,000 times) using a color laser microscope "VK-8500" (Keyence Corporation), and calculating the arithmetic average value thereof.

[0040] <Belt surface condition> Next, the surface state of the belt in the present invention will be described. FIG. 4A is an enlarged schematic view showing a cross section of the intermediate transfer belt, and FIG. 4B is an enlarged schematic view of the surface of the intermediate transfer belt observed from above. As already mentioned, the intermediate transfer belt has a flexible elastic layer 12 laminated on a base layer 11, and spherical particles 13 of uniform diameter are arranged (embedded) independently and orderly in the surface direction on the elastic layer on the outermost surface. Particles are hardly overlapped in the surface direction or the layer thickness direction. It is preferable that the cross-sectional diameter of each particle constituting this surface is uniform, and specifically, the distribution width is preferably ±(average diameter × 0.5) μm or less. To form this, it is preferable to use particles with as uniform a particle size as possible, but even if this is not used, the surface may be formed by a method that can selectively form particles of a certain particle size on the surface, thereby achieving the particle size distribution range. The particle occupies preferably 60% or more of the surface area of ​​the elastic layer 12. If it is less than 60%, the resin portion is too exposed and the toner comes into contact with the rubber, making it difficult to obtain good transferability.

[0041] In the present invention, the spherical resin particles are partially embedded in the elastic layer, and the embedment rate is preferably more than 50% and less than 100%, and more preferably 51% to 90%. By exceeding 50%, the particles are less likely to fall off during long-term use in an image forming apparatus, and durability is excellent. On the other hand, by being less than 100%, the effect of the particles on transferability is not reduced, which is preferable.

[0042] The embedment rate refers to the rate at which a particle is embedded in the elastic layer in the diameter in the depth direction, but the embedment rate mentioned here does not mean that all particles are embedded at more than 50% but less than 100%, but rather the average embedment rate when viewed in a certain field of view may be more than 50% but less than 100%. However, when the embedment rate is 50%, almost no particles are observed that are completely embedded in the elastic layer in cross-sectional observation using an electron microscope (the percentage of particles that are completely embedded in the elastic layer is preferably 5% or less of the total particles).

[0043] Next, an example of a method for producing the belt having the above-mentioned configuration of the present invention will be described. First, a method for producing the base layer 11 will be described.

[0044] A method for producing a base layer using a coating fluid containing at least a resin component of the present invention, that is, a coating fluid containing the polyimide resin precursor or polyamideimide resin precursor, will be described. While slowly rotating a cylindrical mold, for example, a cylindrical metal mold, a coating liquid containing at least a resin component (for example, a coating liquid containing a polyimide resin precursor or a polyamideimide resin precursor) is applied and cast (formed a coating film) uniformly over the entire outer surface of the cylinder using a liquid supplying device such as a nozzle or dispenser. Thereafter, the rotation speed is increased to a predetermined speed, and when the predetermined speed is reached, the speed is maintained constant and the rotation is continued for a desired time. Then, while rotating, the temperature is gradually increased and the solvent in the coating film is evaporated at a temperature of about 80°C to 150°C. In this process, it is preferable to efficiently circulate and remove atmospheric vapor (volatilized solvent, etc.). When a self-supporting film is formed, the mold is transferred to a heating furnace (calcination furnace) capable of high-temperature treatment, the temperature is increased stepwise, and finally a high-temperature heat treatment (calcination) of about 250°C to 450°C is performed to sufficiently imidize or polyamide-imidize the polyimide resin precursor or polyamideimide resin precursor. After sufficient cooling, the elastic layer 12 is subsequently laminated.

[0045] The elastic layer 12 can be manufactured by applying a rubber coating material obtained by dissolving rubber in an organic solvent onto the base layer 11, and then drying and vulcanizing the solvent. As for the coating forming method, existing coating methods such as spiral coating, die coating, and roll coating can be applied, as with the base layer 11, but in order to improve the unevenness transferability, it is necessary to increase the thickness of the elastic layer. As a coating method for forming a thick film, die coating and spiral coating are excellent, and as described above, spiral coating is excellent in that the thickness of the elastic layer 12 can be easily changed in the width direction. Therefore, spiral coating will be described here. First, while rotating the base layer 11 in the circumferential direction, a rubber coating material is continuously supplied from a round or wide nozzle, and the nozzle is moved in the axial direction of the base layer 11 to apply the coating material in a spiral shape onto the base layer 11. The coating material applied in a spiral shape onto the base layer 11 is dried while being leveled by maintaining a predetermined rotation speed and drying temperature. The film is then vulcanized (crosslinked) at a specified vulcanization temperature to form the film. The thickness of the film in the width direction can be changed by changing the nozzle discharge amount, the distance between the nozzle and the die, or by changing the rotation speed of the die. Figure 4 shows a schematic diagram of a belt made in this way.

[0046] <Belt surface preparation method> The vulcanized elastic layer is then sufficiently cooled, and subsequently, spherical particles are applied onto the elastic layer 12 to form spherical particles 13, thereby obtaining the desired seamless belt (intermediate transfer belt). As shown in FIG. 5, a method for forming a layer made of spherical particles is to install a powder supplying device 35 and a pressing member 33, and while rotating, spherical particles 34 are uniformly sprinkled on the surface from the powder supplying device 35, and the spherical particles 34 sprinkled on the surface are pressed with a constant pressure by the pressing member 33. The pressing member 33 embeds the particles in the resin layer while removing excess particles. In the present invention, since monodisperse spherical particles are used in particular, it is possible to form a uniform single particle layer with a simple process of only a smoothing process by such a pressing member. The embedment rate is adjusted by the length of time the pressing member is pressed here.

[0047] The embedment rate of the particles in the elastic layer 12 may be adjusted by other methods, but for example, it can be easily achieved by adjusting the pressing force of the pressing member 33. For example, although it depends on the viscosity of the casting coating liquid, the solid content, the amount of the solvent used, the particle material, etc., as a guideline, when the viscosity of the casting coating liquid is 100 mPa·s to 100,000 mPa·s, the embedment rate of 50% to 100% can be relatively easily achieved by setting the pressing force in the range of 1 mN / cm to 1000 mN / cm. The spherical particles are uniformly arranged on the surface of the elastic layer 12, and then the layer is heated at a predetermined temperature for a predetermined time while rotating to harden the layer and form an elastic layer with the particles embedded in it. After sufficient cooling, the layer is detached from the mold together with the base layer 11 to obtain the desired seamless belt (intermediate transfer belt).

[0048] <Method for measuring the embedment rate of spherical particles in an intermediate transfer belt> The method for measuring the embedment rate of the spherical particles in the intermediate transfer belt is not particularly limited and can be appropriately selected depending on the purpose. For example, the embedment rate can be measured by observing the cross section of the intermediate transfer belt with a scanning electron microscope (SEM).

[0049] <Image forming device> The image forming apparatus of the present invention comprises an image carrier on which a latent image is formed and capable of carrying a toner image, a developing means for developing the latent image formed on the image carrier with toner, an intermediate transfer belt onto which the toner image developed by the developing means is primarily transferred, and a transfer means for secondarily transferring the toner image carried on the intermediate transfer belt to a recording medium, and further comprises other means appropriately selected as necessary, such as a discharging means, a cleaning means, a recycling means, a control means, etc. In this case, it is preferable that the image forming apparatus is a full-color image forming apparatus, in which a plurality of latent image carriers each having a developing means for each color are arranged in series.

[0050] The seamless belt used in the belt component installed in the image forming apparatus of the present invention will be described in detail below with reference to a schematic diagram of the main part. Note that the schematic diagram is only an example and the present invention is not limited thereto.

[0051] FIG. 6 is a schematic diagram of a main part for explaining an image forming apparatus equipped with a seamless belt, which is an intermediate transfer belt according to the present invention, as a belt member. 6 includes an intermediate transfer unit 500 including a belt member, which is configured with an intermediate transfer belt 501, which is an intermediate transfer body stretched over a plurality of rollers, etc. Around this intermediate transfer belt 501, a secondary transfer bias roller 605, which is a secondary transfer charge applying means of the secondary transfer unit 600, a belt cleaning blade 504, which is an intermediate transfer belt cleaning means, a lubricant application brush 505, which is a lubricant application member of a lubricant application means, etc. are arranged to face each other.

[0052] Also, position detection marks are provided on the outer circumferential surface or inner circumferential surface of intermediate transfer belt 501. However, for the outer circumferential surface side of intermediate transfer belt 501, it is necessary to devise a way to provide the position detection marks so as to avoid the passing area of ​​belt cleaning blade 504, which may pose difficulties in arrangement, and in that case, the position detection marks may be provided on the inner circumferential surface side of intermediate transfer belt 501. Optical sensor 514 as a mark detection sensor is provided at a position between primary transfer bias roller 507 and belt drive roller 508, around which intermediate transfer belt 501 is stretched.

[0053] This intermediate transfer belt 501 is stretched around a primary transfer bias roller 507, which is a primary transfer charge applying means, a belt drive roller 508, a belt tension roller 509, a secondary transfer opposing roller 510, a cleaning opposing roller 511, and a feedback current detection roller 512. Each roller is made of a conductive material, and each roller other than the primary transfer bias roller 507 is grounded. A transfer bias controlled to a predetermined current or voltage according to the number of overlapping toner images is applied to the primary transfer bias roller 507 by a primary transfer power source 801 controlled to a constant current or constant voltage.

[0054] The intermediate transfer belt 501 is driven in the direction of the arrow by a belt drive roller 508 which is rotated in the direction of the arrow by a drive motor. The intermediate transfer belt 501, which is the belt member, is usually made of a semiconductor or an insulator and has a single-layer or multi-layer structure, but in the present invention, a seamless belt is preferably used, which improves durability and enables excellent image formation. In addition, the intermediate transfer belt is set to be larger than the maximum paper passable size in order to overlap the toner images formed on the photosensitive drum 200.

[0055] The secondary transfer bias roller 605, which is a secondary transfer means, is configured to be capable of being brought into contact with and separated from the outer circumferential belt surface of the intermediate transfer belt 501 at a portion stretched around the secondary transfer opposing roller 510 by a contact / separation mechanism, which serves as a contact / separation means, which will be described later. The secondary transfer bias roller 605 is disposed so as to sandwich the transfer paper P, which is a recording medium, between the intermediate transfer belt 501 at a portion stretched around the secondary transfer opposing roller 510, and a predetermined transfer bias current is applied by a secondary transfer power source 802 that is constant current controlled.

[0056] The registration roller 610 feeds the transfer paper P, which is a transfer material, between the secondary transfer bias roller 605 and the intermediate transfer belt 501 stretched around the secondary transfer opposing roller 510 at a predetermined timing. A cleaning blade 608, which is a cleaning means, is in contact with the secondary transfer bias roller 605. The cleaning blade 608 removes any deposits adhering to the surface of the secondary transfer bias roller 605 to clean it.

[0057] In a color copier having such a configuration, when an image formation cycle is started, the photoconductor drum 200 is rotated in the counterclockwise direction indicated by the arrow by a drive motor (not shown), and a Bk (black) toner image, a C (cyan) toner image, an M (magenta) toner image, and a Y (yellow) toner image are formed on the photoconductor drum 200. The intermediate transfer belt 501 is rotated in the clockwise direction indicated by the arrow by a belt drive roller 508. As the intermediate transfer belt 501 rotates, the Bk toner image, the C toner image, the M toner image, and the Y toner image are primarily transferred by a transfer bias due to a voltage applied to a primary transfer bias roller 507, and finally, the toner images are superimposed and formed on the intermediate transfer belt 501 in the order of Bk, C, M, and Y.

[0058] For example, the Bk toner image is formed as follows. In FIG. 6, the charger 203 uniformly charges the surface of the photoconductor drum 200 to a predetermined potential with negative charges by corona discharge. Based on the belt mark detection signal, timing is determined, and a writing optical unit (not shown) performs raster exposure with laser light based on a Bk color image signal. When this raster image is exposed, the exposed portion of the surface of the photoconductor drum 200, which was initially uniformly charged, loses charge proportional to the amount of exposure light, and a Bk electrostatic latent image is formed. When the negatively charged Bk toner on the developing roller of the Bk developer 231K comes into contact with this Bk electrostatic latent image, the toner does not adhere to the portion of the photoconductor drum 200 where the charge remains, but adheres to the portion without charge, i.e., the exposed portion, and a Bk toner image similar to the electrostatic latent image is formed.

[0059] The Bk toner image thus formed on the photoconductor drum 200 is primarily transferred onto the outer circumferential belt surface of the intermediate transfer belt 501, which is rotated at a constant speed while in contact with the photoconductor drum 200. A small amount of untransferred residual toner remaining on the surface of the photoconductor drum 200 after this primary transfer is cleaned by the photoconductor cleaning device 201 in preparation for reuse of the photoconductor drum 200. On the photoconductor drum 200 side, the Bk image forming process is followed by a C image forming process, where the color scanner starts reading the C image data at a predetermined timing, and a C electrostatic latent image is formed on the surface of the photoconductor drum 200 by laser light writing using the C image data.

[0060] Then, after the trailing edge of the previous Bk electrostatic latent image has passed and before the leading edge of the C electrostatic latent image has arrived, the revolver developing unit 230 rotates, the C developing unit 231C is set to the developing position, and the C electrostatic latent image is developed with C toner. After that, the development of the C electrostatic latent image area continues, but when the trailing edge of the C electrostatic latent image has passed, the revolver developing unit rotates in the same manner as the previous Bk developing unit 231K, and the next M developing unit 231M is moved to the developing position. This is also completed before the leading edge of the next Y electrostatic latent image arrives at the developing position. Note that the M and Y image forming processes are omitted because the operations of reading color image data, forming electrostatic latent images, and developing are the same as those of the Bk and C processes described above.

[0061] The Bk, C, M, and Y toner images thus formed successively on the photoconductor drum 200 are aligned and primarily transferred onto the same surface of the intermediate transfer belt 501. As a result, a toner image in which up to four colors are superimposed is formed on the intermediate transfer belt 501. Meanwhile, when the image forming operation is started, the transfer paper P is fed from a paper feed unit such as a transfer paper cassette or a manual feed tray, and waits at the nip of the registration rollers 610. Then, when the leading edge of the toner image on the intermediate transfer belt 501 approaches the secondary transfer section where a nip is formed by the intermediate transfer belt 501 stretched around the secondary transfer opposing roller 510 and the secondary transfer bias roller 605, the registration roller 610 is driven so that the leading edge of the transfer paper P coincides with the leading edge of the toner image, and the transfer paper P is transported along the transfer paper guide plate 601, and the transfer paper P and the toner image are registered.

[0062] In this way, when the transfer paper P passes through the secondary transfer section, the four-color superimposed toner image on the intermediate transfer belt 501 is transferred (secondarily transferred) onto the transfer paper P at once by the transfer bias due to the voltage applied to the secondary transfer bias roller 605 by the secondary transfer power source 802. The transfer paper P is transported along the transfer paper guide plate 601, and is discharged by passing through an opposing portion with a transfer paper discharge charger 606 consisting of a discharge needle arranged downstream of the secondary transfer section, and then is sent toward the fixing device 270 by the belt conveying device 210, which is a belt component. Then, the toner image on the transfer paper P is fused and fixed at the nip portion between the fixing rollers 271 and 272 of the fixing device 270, and then the transfer paper P is sent out of the device body by a discharge roller (not shown) and stacked face up on a copy tray (not shown). The fixing device 270 can also be configured to include a belt component as necessary.

[0063] Meanwhile, the surface of the photoconductor drum 200 after the belt transfer is cleaned by the photoconductor cleaning device 201 and is uniformly neutralized by the neutralization lamp 202. Residual toner remaining on the outer circumferential belt surface of the intermediate transfer belt 501 after the second transfer of the toner image onto the transfer paper P is cleaned by a belt cleaning blade 504. The belt cleaning blade 504 is configured to be brought into contact with and separated from the outer circumferential belt surface of the intermediate transfer belt 501 at a predetermined timing by a cleaning member contact / separation mechanism (not shown).

[0064] A toner seal member 502 that comes into contact with and separates from the outer circumferential belt surface of the intermediate transfer belt 501 is provided on the upstream side of the belt cleaning blade 504 in the moving direction of the intermediate transfer belt 501. This toner seal member 502 receives the toner that has fallen from the belt cleaning blade 504 during cleaning of the residual toner, and prevents the fallen toner from scattering onto the transport path of the transfer paper P. This toner seal member 502 is brought into contact with and separated from the outer circumferential belt surface of the intermediate transfer belt 501 together with the belt cleaning blade 504 by the cleaning member contact / separation mechanism.

[0065] Lubricant 506 scraped off by the lubricant application brush 505 is applied to the outer circumferential belt surface of the intermediate transfer belt 501 from which the residual toner has been removed in this manner. The lubricant 506 is made of a solid material such as zinc stearate, and is disposed so as to be in contact with the lubricant application brush 505. Residual charges remaining on the outer circumferential belt surface of the intermediate transfer belt 501 are removed by a discharging bias applied by a belt discharging brush (not shown) in contact with the outer circumferential belt surface of the intermediate transfer belt 501. The lubricant application brush 505 and the belt discharging brush are adapted to be brought into contact with and separated from the outer circumferential belt surface of the intermediate transfer belt 501 at a predetermined timing by respective contact and separation mechanisms (not shown).

[0066] Here, in the case of repeat copying, the operation of the color scanner and the image formation on the photosensitive drum 200 proceed to the image formation process of the first color (Bk) on the second sheet at a predetermined timing following the image formation process of the fourth color (Y) on the first sheet. In addition, the intermediate transfer belt 501 is arranged so that the Bk toner image on the second sheet is primarily transferred to the area cleaned by the belt cleaning blade 504 on the belt outer circumferential surface following the batch transfer process of the four-color superimposed toner image on the first sheet onto the transfer paper. Thereafter, the operation is the same as that for the first sheet. The above was a copy mode for obtaining a four-color full-color copy, but in the case of the three-color copy mode and two-color copy mode, the same operation as above is performed for the specified color and number of times. In the case of the single-color copy mode, only the developer of the specified color of the revolver development unit 230 is in a developing operation state until the specified number of sheets are completed, and the copy operation is performed while the belt cleaning blade 504 is kept in contact with the intermediate transfer belt 501.

[0067] In the above embodiment, a copier having only one photosensitive drum 1 has been described. However, the present invention can also be applied to an image forming apparatus in which a plurality of photosensitive drums are arranged side by side along a single intermediate transfer belt made of a seamless belt, as shown in the schematic diagram of the essential parts of FIG. 7 as an example configuration. FIG. 7 shows an example of the configuration of a four-drum digital color printer that includes four photoconductor drums 21Bk, 21Y, 21M, and 21C for forming toner images of four different colors (black, yellow, magenta, and cyan).

[0068] 7, the printer main body 10 is composed of an image writing unit 12, an image forming unit 13, and a paper feed unit 14 for forming a color image by an electrophotographic method. An image processing unit processes an image based on an image signal and converts it into each color signal of black (Bk), magenta (M), yellow (Y), and cyan (C) for image formation, and transmits it to the image writing unit 12. The image writing unit 12 is a laser scanning optical system consisting of, for example, a laser light source, a deflector such as a rotating polygon mirror, a scanning imaging optical system, and a group of mirrors, and has four writing optical paths corresponding to each of the above color signals, and writes images according to each color signal onto image carriers (photoconductors) 21Bk, 21M, 21Y, and 21C provided for each color in the image forming unit 13.

[0069] The image forming unit 13 includes photoconductors 21Bk, 21M, 21Y, and 21C, which are image carriers for black (Bk), magenta (M), yellow (Y), and cyan (C). As the photoconductors for each color, OPC photoconductors are usually used. Around each photoconductor 21Bk, 21M, 21Y, and 21C, there are arranged a charging device, an exposure unit for the laser light from the writing unit 12, developing devices 20Bk, 20M, 20Y, and 20C for each color of black, magenta, yellow, and cyan, primary transfer bias rollers 23Bk, 23M, 23Y, and 23C as primary transfer means, a cleaning device (not shown), and a photoconductor charge removing device (not shown). The developing devices 20Bk, 20M, 20Y, and 20C use a two-component magnetic brush development method. The intermediate transfer belt 22, which is a belt component, is interposed between each photoconductor 21Bk, 21M, 21Y, 21C and each primary transfer bias roller 23Bk, 23M, 23Y, 23C, and the toner images of each color formed on each photoconductor are transferred in sequence, superimposed on top of each other.

[0070] On the other hand, the transfer paper P is fed from the paper feed section 14 and then carried by the transfer conveyor belt 50, which is a belt component, via the registration rollers 16. Then, when the intermediate transfer belt 22 and the transfer conveyor belt 50 come into contact with each other, the toner image transferred onto the intermediate transfer belt 22 is secondarily transferred (collectively transferred) by the secondary transfer bias roller 60, which serves as a secondary transfer means. As a result, a color image is formed on the transfer paper P. The transfer paper P on which this color image has been formed is transported by the transfer conveyor belt 50 to the fixing device 15, and after the transferred image is fixed by the fixing device 15, it is discharged outside the printer body.

[0071] Residual toner remaining on the intermediate transfer belt 22 without being transferred during the secondary transfer is removed from the intermediate transfer belt 22 by a belt cleaning member 25. A lubricant applicator 27 is disposed downstream of the belt cleaning member 25. The lubricant applicator 27 is composed of a solid lubricant and a conductive brush that rubs against the intermediate transfer belt 22 to apply the solid lubricant. The conductive brush is in constant contact with the intermediate transfer belt 22 to apply the solid lubricant to the intermediate transfer belt 22. The solid lubricant has the effect of improving the cleaning ability of the intermediate transfer belt 22, preventing the occurrence of filming, and improving durability. EXAMPLES

[0072] The present invention will be described in more detail below based on examples. However, the present invention is not limited to these examples, and appropriate modifications of these examples are also within the scope of the present invention as long as they do not deviate from the gist of the present invention. In the following description, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0073] <Example 1> A base layer coating liquid was prepared as described below, and a seamless belt base layer was produced using this coating liquid. [Preparation of base layer coating liquid] First, a polyimide varnish (U-varnish A; manufactured by Ube Industries), whose main component is a polyimide resin precursor, was mixed with a dispersion of carbon black (Special Black 4; manufactured by Evonik Degussa) that had been dispersed in advance in N-methyl-2-pyrrolidone using a bead mill so that the carbon black content was 17% of the polyamic acid solids, and the mixture was thoroughly stirred to prepare [Coating Solution A for Base Layer].

[0074] [Preparation of polyimide base belt] Next, a metallic cylindrical support having an outer diameter of 500 mm and a length of 400 mm, the outer surface of which had been roughened by blasting, was used as a mold and attached to a roll coater. Next, [Base layer coating liquid A] was poured into a pan, and the coating was pumped up at a rotation speed of the coating roller of 40 mm / sec. The gap between the regulating roller and the coating roller was set to 0.6 mm to control the coating thickness on the coating roller. Then, the rotation speed of the cylindrical support was controlled to 35 mm / sec and brought close to the coating roller, with a gap of 0.4 mm between the coating roller and the cylindrical support, and the coating material on the coating roller was uniformly transferred and coated onto the cylindrical support. Then, while continuing to rotate, the cylindrical support was placed in a hot air circulation dryer, gradually heated to 110°C and heated for 30 minutes, further heated to 200°C and heated for 30 minutes, and the rotation was stopped. Then, the cylindrical support was introduced into a heating furnace (sintering furnace) capable of high-temperature treatment, and heated stepwise to 320°C and heated (sintered) for 60 minutes. After sufficient cooling, a polyimide base layer belt A with a film thickness of 60 μm was obtained.

[0075] "Preparation of elastic layer on polyimide base belt" A rubber composition was prepared by blending and kneading the components according to the formulation shown below.

[0076] Acrylic rubber (NipolAR12, manufactured by Nippon Zeon Co., Ltd.): 100 parts Stearic acid (NOF Corp., Beads, Camellia Stearic Acid): 1 part Flame retardant (magnesium hydroxide [Kyowa Chemical Industry Co., Ltd. KISUMA5]): 60 parts Crosslinking agent (hexamethylenediamine carbamate): 0.6 parts DuPont Dow Elastomers Japan Diak.No1 Crosslinking accelerator: 0.6 parts Safic alcan VULCOFAC ACT55 (70% 1,8-diazabicyclo(5,4,0)undecene-7 salt with dibasic acid, 30% amorphous silica) Ionic Conductive Agent: 0.3 parts Butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide (Nippon Carlit Co., Ltd. CIL-312)

[0077] Next, the rubber composition thus obtained was dissolved in an organic solvent (MIBK: methyl isobutyl ketone) to prepare a rubber solution with a solid content of 35%. The prepared rubber solution was applied spirally onto the polyimide base layer while rotating the cylindrical support on which the previously prepared polyimide base layer was formed, by continuously discharging the rubber coating material from a nozzle and moving it in the axial direction of the support. The coating amount was set to a liquid amount such that the final film thickness was 400 μm. Thereafter, the cylindrical support on which the rubber coating material was applied was placed in a hot air circulation dryer while rotating, and heated to 90° C. at a heating rate of 4° C. / min and heated for 30 minutes.

[0078] Next, spherical melamine resin particles (Eposter S12: Nippon Shokubai Co., Ltd.) with an average particle size of 1.2 μm were evenly spread on the surface of the heated rubber composition using the method of Figure 4, and a polyurethane rubber blade pressing member was pressed against it with a pressing force of 100 mN / cm to fix it to the elastic layer. Next, the product was again placed in the hot air circulation dryer, heated to 170°C at a heating rate of 4°C / min, and heat-treated for 60 minutes to obtain [Intermediate transfer belt A].

[0079] <Example 2> An intermediate transfer belt B was obtained in the same manner as in Example 1, except that aluminum hydroxide (Nippon Light Metal Co., Ltd. BF-013) was used instead of magnesium hydroxide.

[0080] <Example 3> An intermediate transfer belt C was obtained in the same manner as in Example 1, except that the melamine spherical resin particles in Example 1 were replaced with acrylic spherical resin particles (Techpolymer SSX-101: manufactured by Sekisui Plastics Co., Ltd.).

[0081] <Example 4> An intermediate transfer belt D was obtained in the same manner as in Example 1, except that the ion conductive agent was changed to butyl bis hydroxyethyl methyl ammonium bis (trifluoromethanesulfonyl) imide (CIL-R10 manufactured by Nippon Carlit Co., Ltd.).

[0082] <Example 5> An intermediate transfer belt E was obtained in the same manner as in Example 3, except that in Example 3, the flame retardant was changed to aluminum hydroxide (BF-013 manufactured by Nippon Light Metal Co., Ltd.) and the ionic conductive agent was changed to butyl bishydroxyethylmethylammonium bis(trifluoromethanesulfonyl)imide (CIL-R10 manufactured by Nippon Carlit Co., Ltd.).

[0083] <Comparative Example 1> An intermediate transfer belt F was obtained in the same manner as in Example 1, except that the ion conductive agent was changed to tetrabutylammonium perchlorate (QAP-01 manufactured by Nippon Carlit Co., Ltd.).

[0084] <Comparative Example 2> In Example 1, the formulation of the rubber composition was changed to the formulation shown below. Acrylonitrile butadiene rubber: 100 parts (Nipol DN302 manufactured by Nippon Zeon Co., Ltd.) Stearic acid (NOF Corp., Beads Stearic Acid Camellia): 1 part Peroxide (NOF Corp., Percumil 40): 3 parts Zinc oxide (Sakai Chemical Industry Zinc oxide type 2) 5 parts Flame retardant (magnesium hydroxide [Kyowa Chemical Industry Co., Ltd. KISUMA5]): 60 parts Ionic Conductive Agent: 0.3 parts Butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide (Nippon Carlit Co., Ltd. CIL-312)

[0085] Next, the rubber composition thus obtained was dissolved in cyclohexanone to prepare a rubber solution with a solid content of 35%. The rubber solution thus prepared was applied to the polyimide base layer by continuously ejecting the rubber coating material from a nozzle while rotating the cylindrical support on which the polyimide base layer had been formed, and moving the rubber coating material in the axial direction of the support to apply the rubber coating material in a spiral shape. The amount of coating was set to a liquid amount such that the final film thickness was 400 μm. Then, the cylindrical support on which the rubber coating material had been applied was placed in a hot air circulation dryer while rotating, and heated to 90° C. at a heating rate of 4° C. / min and heated for 30 minutes. Thereafter, the intermediate transfer belt G was obtained in the same manner as in Example 1.

[0086] [evaluation] (Vertical white stripes) The intermediate transfer belts A to G of the above-mentioned Examples and Comparative Examples were mounted on the image forming apparatus of FIG. 7, and 20,000 sheets of A4 size paper were passed through using OK Topcoat Matte N (Oji Paper Co., Ltd.), a thick coated paper that is prone to particle drop at the paper edge. After that, A3 size paper was passed through and the vertical stripe blank image of A4 width was confirmed. Evaluation was performed according to the following evaluation criteria. <Evaluation criteria> ◎: No vertical stripes or blank areas on the image Good: There are slight vertical white lines, but the print is still usable. ×: Vertical stripes and white spots are so severe that they are practically unusable.

[0087] (Particle residual rate) The detachment of particles was observed with a laser microscope before and after the paper was passed in the evaluation of the vertical streak and white spot, and the residual rate of particles was calculated.

[0088] The results are shown in Table 1. The abbreviations in the table have the following meanings. ACM: Acrylic rubber (NipolAR12 manufactured by Nippon Zeon Co., Ltd.) NBR: Acrylonitrile butadiene rubber (Nipol DN302 manufactured by Nippon Zeon Co., Ltd.) · CIL-312: Butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide (Ion conductive agent manufactured by Nippon Carlit Co., Ltd.) CIL-R10: Butyl bis(hydroxyethylmethylammonium) bis(trifluoromethanesulfonyl)imide (Ion conductive agent manufactured by Nippon Carlit Co., Ltd.) QAP-01: Tetrabutylammonium perchlorate (manufactured by Nippon Carlit Co., Ltd.)

[0089] [Table 1]

[0090] As described above, by adopting the configuration of the present invention, it is possible to provide an intermediate transfer belt that has high durability and flame retardancy so that particles do not fall off even at the edge of the paper, and an intermediate transfer type image forming apparatus that is suitable for forming full-color images using the intermediate transfer belt.

[0091] For example, aspects of the present invention are as follows. (1) An intermediate transfer belt onto which a toner image obtained by developing a latent image formed on an image carrier with a toner is transferred, The intermediate transfer belt has a laminated structure including, from the inside, a base layer and an elastic layer having an uneven surface formed of spherical particles on the outer surface, in that order. the elastic layer contains an acrylic rubber and an ionic conductive agent, The anion component of the ion conductive agent is bis(trifluoromethanesulfonyl)imide (TFSI). The intermediate transfer belt is characterized by the above-mentioned. (2) The intermediate transfer belt according to (1) above, wherein the cationic component of the ion conductive agent is butyl bis hydroxyethyl methyl ammonium or butyl-3-methylpyridinium. (3) The intermediate transfer belt according to (1) or (2), wherein the elastic layer of the intermediate transfer belt contains aluminum hydroxide. (4) The intermediate transfer belt according to any one of (1) to (3) above, wherein the spherical particles of the intermediate transfer belt contain an acrylic resin. (5) The intermediate transfer belt according to any one of (1) to (4) above, wherein the intermediate transfer belt is a seamless belt. (6) An image forming apparatus comprising: an image carrier on which a latent image is formed and capable of carrying a toner image; a developing means for developing the latent image formed on the image carrier with toner; an intermediate transfer belt onto which the toner image developed by the developing means is primarily transferred; and a transfer means for secondarily transferring the toner image carried on the intermediate transfer belt to a recording medium, wherein the intermediate transfer belt is an intermediate transfer belt as described in any one of (1) to (6) above. (7) The image forming apparatus according to (6) above, wherein the image forming apparatus is a full-color image forming apparatus, and comprises a plurality of latent image carriers, each having a developing means for each color, arranged in series. [Explanation of symbols]

[0092] (Symbols in Figure 4) 11 Base layer 12 Elastic layer 13 Spherical particles

[0093] (Symbols in Figure 5) 31 Metal Drum 32 Belt with base layer and elastic layer 33 Pressing member 34 Spherical particles 35 Powder feeding device

[0094] (Symbols in Figure 6) 70 Antistatic roller 80 Earth Roller 200 Photoconductor drum 201 Photoconductor cleaning device 202 Static electricity removal lamp 203 Charger 204 Potential Sensor 205 Image density sensor 210 Belt conveyor 230 Revolver developing unit 231Y Y developing machine 231K Bk developing machine 231C C developing machine 231M M developing machine 270 Fixing device 271, 272 Fixing roller 500 Intermediate Transfer Unit 501 Intermediate transfer belt 502 Toner seal material 503 Charger 504 Belt cleaning blade 505 Lubricant application brush 506 Lubricants 507 Primary transfer bias roller 508 Belt drive roller 509 Belt tension roller 510 Secondary transfer opposing roller 511 Cleaning opposing roller 512 Feedback current detection roller 513 Toner Image 514 Optical Sensor 600 Secondary Transfer Unit 601 Transfer paper guide plate 605 Secondary transfer bias roller 606 Transfer paper static eliminator charger 608 Cleaning Blade 610 Registration roller 801 Primary transfer power supply 802 Secondary transfer power supply P Transfer paper L Laser light

[0095] (Reference symbols in Fig. 7) 10 Printer body 12 Image writing section 13 Image forming section 14 Paper feed section 15 Fixing device 16 Registration roller 20Bk, 20M, 20Y, 20C developing device 21Bk, 21M, 21Y, 21C photoconductor 22 Intermediate transfer belt 23Bk, 23M, 23Y, 23C Primary transfer bias roller 25 Belt cleaning material 26 Drive roller 27 Lubricant application device 50 Transfer conveyor belt 60 Secondary transfer bias roller P Transfer paper L Laser light [Prior art documents] [Patent documents]

[0096] [Patent Document 1] Japanese Patent Application Publication No. 9-230717 [Patent Document 2] JP 2002-162767 A [Patent Document 3] JP 2004-354716 A [Patent Document 4] JP 2007-328165 A [Patent Document 5] JP 2009-75154 A [Patent Document 6] Patent No. 6918688

Claims

1. An intermediate transfer belt onto which a toner image obtained by developing a latent image formed on an image carrier with a toner is transferred, The intermediate transfer belt has a laminated structure including, from the inside, a base layer and an elastic layer having an uneven surface formed of spherical particles on the outer surface, in that order. the elastic layer contains an acrylic rubber and an ionic conductive agent, The anion component of the ion conductive agent is bis(trifluoromethanesulfonyl)imide (TFSI). The intermediate transfer belt is characterized by the above-mentioned.

2. 2. The intermediate transfer belt according to claim 1, wherein the cationic component of the ionic conductive agent is butyl bis hydroxyethyl methyl ammonium or butyl-3-methylpyridinium.

3. 3. The intermediate transfer belt according to claim 1, wherein the elastic layer of the intermediate transfer belt comprises aluminum hydroxide.

4. 3. The intermediate transfer belt according to claim 1, wherein the spherical particles of the intermediate transfer belt comprise an acrylic resin.

5. 3. The intermediate transfer belt according to claim 1, which is a seamless belt.

6. 3. An image forming apparatus comprising: an image carrier on which a latent image is formed and capable of carrying a toner image; a developing means for developing the latent image formed on the image carrier with toner; an intermediate transfer belt onto which the toner image developed by the developing means is primarily transferred; and a transfer means for secondarily transferring the toner image carried on the intermediate transfer belt to a recording medium, wherein the intermediate transfer belt is the intermediate transfer belt according to claim 1 or 2.

7. 7. The image forming apparatus according to claim 6, wherein the image forming apparatus is a full-color image forming apparatus, and comprises a plurality of latent image carriers, each having a developing means for each color, arranged in series.

Citation Information

Patent Citations

  • Intermediate transfer of small toner particle

    JP1997230717A

  • Image carrier, image recording device using the same, and method for recording image

    JP2002162767A

  • Color image forming apparatus

    JP2004354716A

  • Conductive endless belt

    JP2007328165A

  • Conductive endless belt

    JP2009075154A